Post Covid 19 Pandemic: The Contribution of Zakat, Infaq, and AIms to The Country’s Economy - Dyarini, Dyarini; Raizha Utari, Natya (Journal Research of Social Science, Economics, and Management, 2024)
The COVID-19 pandemic, which began in early 2020, has had many impacts on humanity around the world. This crisis resulted in a decrease in household consumption, a decrease in investment due to economic uncertainty, a decrease in investment, and public consumption. In the context of the COVID-19 pandemic, zakat, infaq, and alms (ZIS) contribute by providing direct assistance to affected mustahiks, strengthening the economy through empowering MSMEs, and supporting the health and education sectors to overcome equitable economic impacts. This study aims to analyze the role of zakat, infaq, and alms (ZIS) management institutions in helping the country's economy after the COVID-19 pandemic in Indonesia. The research method used in this study is descriptive assisted by literature study. The results showed that the Zakat Management Institute (ZIS) played a vital role in responding to and overcoming the impact of the Covid-19 pandemic in Indonesia, despite facing several challenges in fund distribution and optimization. Close collaboration between the government, communities, and Zakat Management Organizations (OPZIS) is key in ensuring effective distribution of funds, while zakat empowerment through digital innovation and Cash for Work (CFW) programs is a solution to reduce the impact of health and economic crises, making a positive contribution to more equitable and sustainable economic development.